O ensino de Geografia nos programas paranaenses de pós-graduação stricto sensu em Geografia - Novais, Éliton Paulo (2020)
This paper aims to evidence the academic production about Geography Teaching in stricto sensu post-graduation programs at federal and state universities in the State of Paraná, Brazil. The methodology adopted to carry on this study is characterized as a qualitative approach and, based on the state-of-the-art type of research, resources from documentary research were applied for data collection. In Brazil, as well as in other countries, Geography was composed and stablished first at schools and it was only afterwards that it reached the universities. In the last decades of the 20th century, the studies on Geography Teaching have increased, especially for considering the changes required in the curricular guidelines. At the same time, Higher Education in Brazil experiences a growth as never seen before. The stricto sensu postgraduation programs in Geography, which were only 15 in 1990, are 76 now (2020), with at least one program for each federative unit. In the State of Paraná, the first program started only in 1998. If compared to other research areas and to other states, one can say the stricto sensu post-graduation courses in Geography in the state started late, to a certain extent. Currently, the State of Paraná has 7 programs, including 7 doctorate courses and 6 master's degree courses. Among these 7 programs, only 2 present the field of study specifically focused to Geography Teaching; only 1 keeps it active. Even though there is only one program with the specific field of study, it was possible to verify through the years (1998-2018), in all the programs, among dissertations and theses, the production of 132 studies about the theme. What indicates that, regardless the specific field of study, there is a group of researchers committed to the theme. The most approached foci in these 132 productions were: Teacher’s education and practice (34 productions), Methodologies (25 productions), Environmental Education (24 productions) and Concept Formation (22 productions). This research aims at promoting the debate on where is the place of Geography Teaching in Geographic Science, to enhance the product of the academic research in the area, reaffirming its importance in scientific, academic, and school contexts; and also at pointing a Direction to the studies of those who are interested in the subject and wish to work with it.